Internship Experience and Social Environment in Encouraging HR Readiness to Enter The Labor Market: Evidence From College Graduate - Podungge, Robiyati; Tantawi, Rezkiawan; Liho, Rasmi (Jambura Science of Management, 2025)
Purpose: Employment plays a pivotal role in driving social and economic development, particularly in Gorontalo Province, which faces significant challenges in integrating university graduates into the labor market. This study focuses on analyzing the influence of internship experiences and social environment on the job readiness of graduates from Universitas Negeri Gorontalo who graduated between 2021 and 2023.Design/Methodology/Approach: This study employed a quantitative method with multiple regression analysis techniques. It involved 1,618 respondents who were graduates of Universitas Negeri Gorontalo from the 2021–2023 period.Findings: The findings indicate that while internship experiences have proven effective in providing relevant practical skills, the role of social networks, such as family and community support, has a more significant influence on graduates' readiness to enter the workforce. The study recommends that universities enhance the quality of internship programs through strategic partnerships with various industries, particularly those experiencing growth. Additionally, strengthening professional social networks for graduates is essential to support their transition into the labor market. Moving forward, further research is encouraged to explore other factors influencing job readiness, enabling more comprehensive and impactful solutions to be developed.